In vitro and in vivo genotoxicity assessment of the dopamine receptor antagonist molindone hydrochloride. (4th April 2016) - Krishna, Gopala; Gopalakrishnan, Gopa; Goel, Saryu
Abstract : Molindone hydrochloride is a dihydroindolone neuroleptic with dopamine D2 and D5 receptor antagonist activity. As an integral component of its preclinical safety evaluation, molindone hydrochloride was evaluated in a series of in vitro and in vivo genetic toxicology assays. In the bacterial reverse gene mutation assays employing four Salmonella tester strains (TA98, TA100, TA1535, and TA1537) and the E. coli tester strain WP2uvrA, molindone hydrochloride was negative in all strains, except TA100, in which it induced a positive response (up to 3‐fold) in the presence of rat liver S9. With human S9, a small (2‐fold), but nonreproducible, increase in revertants was observed in TA100 at the highest concentration of molindone tested (5, 000 µg/plate). The mutagenicity was completely abrogated by the addition of glutathione and UDP‐glucuronic acid to rat liver S9, suggesting detoxification of the mutagenic metabolite(s) by Phase II conjugation reactions, pathways commonly operational in humans. Molindone hydrochloride did not induce chromosomal aberrations in human lymphocyte cultures, did not elicit a positive response in a rat bone marrow micronucleus test for clastogencity/aneugenicity, and did not give a positive response in the rat liver comet assay for DNA damage. Collectively, the weight of evidence from these studies, combined with a large margin of safety and efficient detoxification through Phase II conjugation supports the interpretation that molindone hydrochloride does not pose a genotoxic risk to humans at the anticipated clinical dose levels. Environ. Mol. Mutagen. 57:288–298, 2016. © 2016 Wiley Periodicals, Inc.